STUDY OF HOUSEHOLD POVERTY OF THE FISHERMAN LABORS IN THE VILLAGE OF HALANG MUKA ISLAND KUBU BABUSSALAM DISTRICT ROKAN HILIR REGENCY RIAU PROVINCE - Syaputra, Deni; Hendri, Ridar; Nugroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in April until May 2017 at Halang Muka Island village. The purpose of this study is to find out the level of poverty, describe the condition of poverty, and to provide poverty reduction advice. The research method is using a combination of qualitative and quantitative methods, and using descriptive analysis.The results of this study indicate that the average household of working fishermen is categorized as poor. The causes of fisherman poverty are: (1) low fishery production (2) low fisherman household income, (3) alternative employment less (4) limited capital (5) low education level, (6) fishermen still dependent on ship owner, 7) A large family load and (8) wasteful consumption patterns. The Rokan Hilir Government's efforts to combat fishing communities include fishing equipment, such as ships, nets and from central government such as Bantuan Langsung Tunai, Beras Sejahtera, Asuransi Nelayan and Pengembangan Usaha Mina Perikanan. In the implementation of the aid is still loaded with nepotism so that the aid target is not accurate. Implications of mitigation that can be done are: (1) Improve knowledge of fishermen community with socialization and training, (2) Guidance from professional fisheries extension workers, (3) growth and development of Kelompok Usaha Bersama (4) Facilitate fishermen access to capital, (5) Creating alternative business and (5) Increasing participation of wife of fisherman to household income. Keywords: Fisherman, Cause of Poverty, Poverty Alleviation, Halang Muka Island.